Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 4 No 3 (2018): KIU Journal of Social Sciences, Vol. 4 No. 3, September 2018, 2018)
This issue of KIU Journal of Social Sciences focuses on Social Psychology, Educational Psychology, Educational Technology, Political Education as well as Business and Entrepreneurship Studies. Social psychology is the scientific study of how people's thoughts, feelings, and behaviors are influenced by the actual, imagined, or implied presence of others. Social Psychology has an important role in the educational sector. It helps in improvement of teaching techniques, learning practices, intelligence level and cognition skills of students, motivation of students and student-teacher relationship. Poor academic performance of students is mostly due to socio-psychological issues. Restrctive environment, lack of encouragement, punishments, overburden of studies, fear of failure in examination and harsh treatment destroy student’s creativity. That is why the first part of the Journal addresses issues in Social Psychology such as parenting styles, marriage compatibility, cross cultural understading and social media usage and so on. One of the papers argues that students from authoritative parenting have positive attitude than students from other parenting styles. The paper therefore, recommended that teachers should take cognizance of the fact that students are from various homes and with different parenting styles thereby catering for the individual differences that may affect their attitudes to learning. Section two explores the role of technology in teaching and learning. Technology has the ability to enhance relationships between teachers and students. When teachers effectively integrate technology into subject areas, teachers grow into roles of adviser, content expert, and coach. Technology helps make teaching and learning more meaningful and fun. Today, more than ever, the role of educational technology in teaching is of great importance because of the use of information and communication technologies. With the help of various applications for distance education, the Internet, teachers, and students themselves, they see the advantage of educational technology. In today’s world, entrepreneurship is focused on developing knowledge, skills, and understanding of how an innovative and creative idea, product, or process can be used to form a new and successful business or to help an existing firm to grow and expand. ... For this purpose Government also welcomes entrepreneurs to start their business. However, risk taking is a dominant attribute of entrepreneurial activities, as the higher the risk-taking orientation, the higher a firm’s profitability and growth. This is why one of the papers in the last section of this edition establishes the effect of entrepreneurial risk taking on performance of small and medium scale enterprises (SMEs). It recommends that recommends that operators should always identify and assess the trends of the opportunities impending before taking risk not just dare risk as this will help to address the rate at which SMEs managers, owners and staff  take risk, so that risk taking will relate and significantly influence their performance. In all, this issue of KIU Journal of Social Sciences contains papers that have information on various fields of human endeavour. The theoretical and empirical analyses in the papers provide solutions to one societal problem or the other. The authors’ teachings and areas of research must have certainly influenced their perspectives on the diagnoses of the matters they have addressed in their articles.